2007
DOI: 10.1111/j.1471-4159.2007.05146.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential vulnerability of mesencephalic dopamine neurons to glutamate transporter dysfunction

Abstract: Nigral depletion of the main brain antioxidant GSH is the earliest biochemical event involved in Parkinson’s disease pathogenesis. Its causes are completely unknown but increasing number of evidence suggests that glutamate transporters [excitatory amino acid transporters (EAATs)] are the main route by which GSH precursors may enter the cell. In this study, we report that dopamine (DA) neurons, which express the excitatory amino acid carrier 1, are preferentially affected by EAAT dysfunction when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…EAAC1 −/− mice have reduced neuronal glutathione content due to the lack of EAAC1-mediated neuronal cysteine uptake. 9,13,33,34 To assess the level of oxidative stress in EAAC1 −/− midbrain dopaminergic neurons, brain sections were immuno-stained for the presence of nTyr-modified proteins. 35 SNc dopaminergic neurons in the EAAC1 −/− mice showed an increase in nTyr immunoreactivity (Fig 3A, B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EAAC1 −/− mice have reduced neuronal glutathione content due to the lack of EAAC1-mediated neuronal cysteine uptake. 9,13,33,34 To assess the level of oxidative stress in EAAC1 −/− midbrain dopaminergic neurons, brain sections were immuno-stained for the presence of nTyr-modified proteins. 35 SNc dopaminergic neurons in the EAAC1 −/− mice showed an increase in nTyr immunoreactivity (Fig 3A, B).…”
Section: Resultsmentioning
confidence: 99%
“…EAAC1 was diffusely distributed in the midbrain, consistent with its ubiquitous expression over neuronal cell bodies and processes.10,11 However, there was higher EAAC1 expression over dopaminergic (TH-positive) neurons (Fig 4A), in agreement with previous reports. 11,33 Human postmortem midbrain sections were similarly stained for EAAC1 and TH, but for technical reasons the anti-NeuN antibody could not be used with the postmortem tissue. As in the mouse brain, normal human brain showed increased EAAC1 expression in dopaminergic (TH-positive) neurons (see Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extracts from rat striatum were used as a positive control, since the specificity of the antibodies has already been verified in this species (Bender et al, 2001; Kawaguchi and Hirano, 2002; Meier and Grantyn, 2004; Nafia et al, 2008; Rostkowski et al, 2009). Western-blot experiments showed that the antibodies produced bands that were located at the same level in the gel for both rat striatum and tree shrew brain protein extracts.…”
Section: Resultsmentioning
confidence: 99%
“…A deficiency of EAATs has been associated with reduced glutathione (GSH) levels and increased oxidant levels, as well as neurodegeneration in the hippocampus at an advanced age [12]. EAAT dysfunction can trigger GSH depletion, which ensures astrocyte oxidative death and mesencephalic dopamine neuron vulnerability [13,14]. GSH depletion is suggested to be a primary event in the pathogenesis of PD [15].…”
Section: Genomic Factors Associated With Thiamine In Parkinson's Diseasementioning
confidence: 99%